O professor e a prática telecolaborativa no teletandem - Garcia, Daniela Nogueira de Moraes [UNESP] (My University, 2011)
The new technologies have increasingly provided access to foreign languages and cultures and also to authentic communication. If we consider that the foreign languages teaching/learning process and teachers’ education can be enriched by telecollaboration, I believe it is necessary to observe the roles played by language teachers. Based on an ethnographic qualitative study carried out with Brazilian and foreign university students, this paper focuses on teletandem practice, a distance tandem modality carried out by audio and video conferences with resources such as Windows Live Messenger, Skype or ooVoo, to investigate roles played by language teachers in telecollaborative practice. The data were collected from (a) e-mails exchanged between the partners and between partners and the mediator-teacher; (b) DVDs of interaction sessions recordings; (c) written teletandem sessions recordings; (d) recordings of interviews between the partners and the researcher at ooVoo; (e) fi eld notes taken at Teletandem Laboratory at UNESP- Assis; and (f) participants’ written reports. The data analysis, from the hermeneutic interpretative perspective, revealed that the teacher is not ignored but is given new roles to maximize the process towards meaningful and intercultural learning.

As novas tecnologias têm possibilitado acesso às línguas e culturas estrangeiras e, também, à comunicação autêntica, de forma crescente. Se considerarmos que o ensino e a aprendizagem de línguas estrangeiras e a formação dos professores podem ser enriquecidos pela telecolaboração, acredito ser necessário observar os papéis desempenhados por professores de línguas. Baseado em um estudo qualitativo etnográfi co desenvolvido com alunos universitários brasileiros e estrangeiros, este artigo enfoca a prática no teletandem, uma modalidade de tandem à distância realizada via conferências de áudio e vídeo com recursos de aplicativos como Windows Live Messenger, Skype ou ooVoo, para investigar os papéis dos professores de línguas na prática telecolaborativa. Os dados foram coletados de (a) e-mails trocados entre os parceiros e entre parceiros e professor-mediador; (b) DVDs de registros das sessões de interação; (c) registros escritos das sessões de interação; (d) gravações de entrevistas entre parceiros e pesquisadora no ooVoo; (e) notas de campo coletadas no Laboratório de Teletandem da UNESP- Assis e (f) relatos escritos dos participantes. A análise, sob a perspectiva interpretativa da hermenêutica, revelou que o professor não é ignorado, mas a ele são atribuídos novos papéis de modo a maximizar o processo rumo à aprendizagem signifi cativa e intercultural.
The Teacher and Teletandem Telecollaborative Practice
Keywords: New technologies; Teacher’s roles; Teletandem; Foreign language teaching/learning process; Novas tecnologias; Papéis do professor; Teletandem; Processo de ensino/aprendizagem de línguas estrangeiras